Double Life of Roanoke Colony - Vobejda, Patrik (Univerzita Pardubice, 2022)
This thesis explores mysterious disappearance of nearly 155 English settlers, who lived in the very first English colony, Roanoke. It analyses depiction of the mystery in two chosen works. Focal themes this thesis examines are feminism; a genre of horror; politics; native Americans; and its roles in chosen works with relation to Roanoke. Using the analysis method, theoretical findings are consulted with the chosen works.
Dvojí život kolonie Roanoke
Keywords: Roanoke; záhada; horor; feminismus; politika; původní Američané; John White; Roanoke; mystery; horror; feminism; politics; native Americans; John White